Особливості класифікації творів масової літератури - Угольнікова, Наталія Сергіївна; Чухненко, Маргарита В'ячеславівна (НТУ "ХПІ", 2017)
У статті наведено опис жанрів сьогоденної масової літератури, приведено аналіз особливостей кожного з розглянутих жанрів. Показано можливість використання частотного словника як засобу визначення формальних жанрових ознак у творах масової літератури. Особлива увага приділена можливости автоматизувати створення частотних словників для визначення жанрів. Розроблено алгоритм автоматичного вилучення частотних слів, які характерезують відповідний текст, з тесту обраного експертом жанру.

The article explores the approach of dividing the modern literary process into a triad and singles out one of its facets – mass literature. Analyzed the differences in the term "literary genre", an overview of the genres of today’s mass literature, an analysis of the characteristics of each of the genres examined. The notion "frequency dictionary" is considered in the context of applied linguistics and problems that arise in the construction of frequency dictionaries of large text boxes are described. The possibility of using a frequency dictionary as a means of determining formal genre features in works of mass literature is shown. Particular attention is paid to the ability to automate the creation of frequency dictionaries for the definition of genres. An algorithm for automatically extracting frequency words characterizing the corresponding text from the text of the genre chosen by the expert is proposed, which will automate the process of determining the genre of an arbitrary text.
Features of the classification of works of mass literature
Keywords: словник частотний; детектив; фантастика наукова; фентезі; трилер; роман пригодницький; frequency dictionary; detective; science fiction; fantasy; thriller; adventure novel